“FOREIGNIZATION AND DOMESTICATION IN TRANSLATING NATURE DESCRIPTIONS IN JACK LONDON'S WHITE FANG” (Journal of Universal Science Research, 2025)
This paper focuses on the role of stylistic devices and symbolism in nature descriptions in Jack London’s “White Fang” and their recreation in the Uzbek translation. By analyzing selected passages, the study examines the translator’s use of foreignization and domestication strategies in rendering nature imagery.